Structural equation modeling based empirical analysis: direct and indirect effects of job satisfaction on job performance in Jordanian five-star hotels - Fazida, Karim; Mahadzirah, Mohamad; Bandar Ersan, Alown (Global Academic Excellence, 2020)
In order to improve and maintain competitiveness in the hotel sector, the key elements of success must be available, which is headed by an efficient employee, so it is essential that the employees' performance be at its best. This study examined the effect of job satisfaction (JS) on job performance (JP), organisational structure (OS) and leadership style (LS) on (JS), and Quality of work-life (QWL) on (JP) among five-star hotels employees in Jordan. The study also examined the moderating role of quality of work-life on the variable’s relationships. A questionnaire was used as the main instrument for data collection from 430 employees of five-star hotels. Data analysis was conducted with the help of Structural Equation Modelling (SEM) to determine the level of relationships among (JS), (OS), (LS), (JP), and (QWL). According to the obtained findings, there is a positive relationship between JS and QL on JP, and QWL has a partial moderating role in the relationship between JS and JP. The study findings motivate future studies to carry out studies of the same caliber in other sectors of Jordan, and also in other contexts based on different perspectives.